(untitled) (Journal of Social Sciences Review, 2023)
This research endeavoured to realize the objective of identifying possible factors which cause writing anxiety among undergraduate (BS) students of Kohat University of Science and Technology (KUST), situated in Khyber Pakhtoon Khwa (KPK), majoring in English. For this interpretive study, students’ perceptions were obtained by adopting a mixed-methods approach; a questionnaire was accomplished by 101 sample students, whereas 12 participants were engaged in semi-structured interviews. Through triangulation of quantitative and qualitative data, the following main sources of WA were explored: linguistic difficulties, fear of teachers’ negative comments, insufficient writing techniques, insufficient writing practice, time pressure, and lack of background knowledge about the concerned topics. In addition, analysis of qualitative data specified some additional causes: fear of peers’ negative comments, competition, the nature of the audience, and over-dependency on information technology. The contribution of this study is significant either through theoretical and pedagogical implications or with respect to valuable recommendations for future researchers.